2015
DOI: 10.1152/jn.00939.2014
|View full text |Cite
|
Sign up to set email alerts
|

Normalization in human somatosensory cortex

Abstract: Brouwer GJ, Arnedo V, Offen S, Heeger DJ, Grant AC. Normalization in human somatosensory cortex. J Neurophysiol 114: 2588 -2599, 2015. First published August 26, 2015 doi:10.1152/jn.00939.2014.-Functional magnetic resonance imaging (fMRI) was used to measure activity in human somatosensory cortex and to test for cross-digit suppression. Subjects received stimulation (vibration of varying amplitudes) to the right thumb (target) with or without concurrent stimulation of the right middle finger (mask). Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 111 publications
(121 reference statements)
0
28
0
Order By: Relevance
“…Another future direction would be to use encoding models to explicitly characterize pitch and timbre selectivity throughout the auditory cortex and thus explore in more depth how these populations are modulated by attention. These approaches have been successfully used to characterize suppressive stimulus interactions in the visual system (Brouwer and Heeger, 2011) and the somatosensory system (Brouwer et al, 2015) and could be similarly useful in understanding the interactions between representations of pitch and timbre.…”
Section: Discussionmentioning
confidence: 99%
“…Another future direction would be to use encoding models to explicitly characterize pitch and timbre selectivity throughout the auditory cortex and thus explore in more depth how these populations are modulated by attention. These approaches have been successfully used to characterize suppressive stimulus interactions in the visual system (Brouwer and Heeger, 2011) and the somatosensory system (Brouwer et al, 2015) and could be similarly useful in understanding the interactions between representations of pitch and timbre.…”
Section: Discussionmentioning
confidence: 99%
“…Divisive normalisation has proven to be a useful model to explain nonlinear responses in the visual (Heeger, 1991(Heeger, , 1992Albrecht, & Geisler, 1991), olfactory (Olsen, Bhandawat, & Wilson, 2010), and auditory system (Rabinowitz, Willmore, Schnupp, & King, 2011;David, Mesgarani, Fritz, & Shamma, 2009), as well as multisensory (Ohshiro, Angelaki, & DeAngelis, 2011) and even cognitive processes (Louie, Khaw, & Glimcher, 2013;Louie Grattan, & Glimcher, 2011;Reynolds & Heeger, 2009). Although the divisive normalisation model has been classically interpreted as a canonical mechanism for maximising sensitivity (Brouwer, Arnedo, Offen, Heeger, & Grant, 2015) and reducing redundancy (Sinz & Bethge, 2013), our results suggest it could also contribute to perceptual aggregation of multi-component stimuli. Figure 7.…”
Section: Mechanisms Underlying Overestimation Of Multiple Discrepant mentioning
confidence: 74%
“…Interestingly, a recent fMRI study used divisive normalisation models to explain the suppression of somatosensory responses during concurrent stimulations of different digits (Brouwer, Arnedo, Offen, Heeger, & Grant, 2015). In particular, Brouwer and colleagues (2015) speculated that interdigit suppression (i.e.…”
Section: Mechanisms Underlying Overestimation Of Multiple Discrepant mentioning
confidence: 99%
“…Using the LRBN task, we have also previously shown that bimanual processing may be more vulnerable to central perturbations compared to unimanual processing (Convento et al, 2018). These bimanual perceptual interactions, like other bimanual effects that operate in specific feature domains and with other task demands (Craig and Qian, 1997;Braun et al, 2005;Kuroki et al, 2017), are often understood as masking effects that may be explained by divisive normalization computations in the somatosensory system (Brouwer et al, 2015;Rahman and Yau, 2019).…”
Section: Discussionmentioning
confidence: 93%